ANALISIS KINERJA KEUANGAN PADA PT BUKIT BAHARI INDAH - Abdul Wahab; Ahmad Firdaus; Adi Siswanto (Cross-border, 2021)
The research as outlined in this Final Project aims to determine the analysis of financial performance at the company PT Bukit Bahari Indah. The research method used in this study is a quantitative descriptive approach, which is to analyze financial performance with the financial report media for the period 2018-2020 using the current ratio approach. , debt to equity ratio and net profit margin. The results of the research on the financial performance of PT Bukit Bahari Indah, the results obtained for the current ratio for the period 2018-2019 experienced an increasing trend, while in 2019-2020 there was a downward trend. The debt to equity ratio for three years, namely the period 2018-2020, experienced a significant downward trend, while net profit margins also experienced a downward trend for three years.